UMUMIY FIZIKA KURSI BOʻYICHA TALABLARDA TADQIQOTCHILIK KOMPETENSIYASINI SHAKLLANTIRISH - Bekmuratova, M. (SCIENCE and SOCIETY, 2025)
The article discusses the methodology for developing research competence based on solving non-standard problems in general physics by including mini-research. Three levels of development of research competence are identified based on the generality of students’ mental and practical actions in the course of general physics.